Tracing the Mathematical Literacy of Prospective Teachers: Teaching Readiness in the Modern Era - Dirgantoro, Kurnia Putri Sepdikasari; Jupri, Al; Soesanto, Robert Harry (Pendidikan Matematika UNIMOR, 2025)
Mathematical literacy is increasingly recognized as a crucial competency for individuals in navigating real-world problems. However, there remains a gap in understanding how well prospective teachers—future facilitators of learning—possess and apply this competency. This study aims to explore the mathematical literacy levels of prospective teachers and examine their readiness to teach in the context of 21st-century education. A qualitative descriptive approach was employed, involving 241 prospective teachers in many fields as participants. Data were collected using a mathematical literacy test based on four core domains—Numbers and Their Operations, Algebra, Geometry and Measurement, and Data Analysis and Probability—along with an open-ended questionnaire to gain deeper insights into participants' perspectives. The results revealed that the overall mathematical literacy level was relatively low, with an average score of 44.69 out of 100. The highest achievement was found in the domain of Numbers and Their Operations, followed by Data Analysis and Probability, then Algebra, with Geometry and Measurement as the lowest-performing domain. Despite acknowledging the importance of mathematical literacy, many students still face difficulties applying their knowledge to real-life contexts. These findings underscore the urgency to reevaluate teacher education curricula, particularly in systematically integrating mathematical literacy development across relevant courses. Strengthening these aspects may enhance teaching readiness and support prospective teachers in fostering literacy-based learning in future classrooms.